STRATEGI KOMUNIKASI PERSUASIF PALANG MERAH INDONESIA (PMI) RIAU DALAM MENINGKATKAN JUMLAH PENDONOR DARAH SUKARELA - Aditya Eriza Zuhry (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2015)
Blood donor is blood transfusion activity from healthy to the unhealthy person. Riau PMI succeeded in increasing quantity of voluntary blood donors at Pekanbaru City by proactive system,that Riau PMI came around people by blood donor cars that who want to donor for voluntarily. Voluntary blood donors is activity without reward and compulsion from any party. This research aims to know Persuasive communication strategy of Riau PMI to determine persuader and persuade, to increase quantity of voluntary blood donors,to know how they make instruction,channel used and persuasive technique to the Public.This research using qualitative methods with the presentation of descriptive analysis. Informants in this study use five person from Riau PMI. while the research object is Persuasive communication strategy Riau PMI to increase quantity of voluntary blood donors. Data collection techniques used were observation, interview and documentation. To reach out validity data in this research, researcher used extension, participation and triangulation.The results obtained,persuader selected based on expertise in communicating and experience from member and staff of Riau PMI,persuade based on information obtained but no determination of the people who will persuasive method because all people can be invite to blood donor but not necessarily can to do blood donor, message delivered in the form of information about the blood donor by using short language and repeated, so that message delivered in the form of verbal or written, there are three communication persuasive techniques that using by Riau PMI, integrity technique is capability persuader uniting themselves with persuade, the association technique is message delivered using the object of interest, reward techniques is influence by giving profitable tantalizing. That three technique support communication channels face to face and verbal or written message in to pasuasive communication used by Riau PMI. By following Formula AIDDA, Riau PMI conduct persuasive through a rational process which touches the cognitive and emotional aspects of society, in persuasive communication strategy known as psychodynamic strategy.Keywords: Persuasive Communication Strategy, Donor Blood, PMI Riau